Penerapan Activity Based Costing Sebagai Dasar Penentuan Harga Jual Produk UMKM - Olivia, Hastuti (TIN: Terapan Informatika Nusantara, 2020)
The company organization needs to conduct an analysis of the operational costs needed, with profit and income, the company's organizational operations will continue to run. Likewise with MSMEs which are the most developed organizations in Indonesia today. The role of MSMEs is very important in the economic sector, where MSMEs are the main pillars of economic improvement. The purpose of the UMKM is to get a profit or profit so that the operational process continues. Profit is obtained from product sales minus production costs, so determining the selling price of the product is very important. Prices that are too high will reduce consumer buying interest and prices that are too low will have an impact on profits. Therefore, MSMEs must make efforts such as analyzing the selling price of the product and controlling the costs incurred as a whole in the production process. In this case the economic technique using the Activity Based Costing method has a role in the analysis process to determine the selling price of the product. The ABC method calculates the basic cost of products to determine the selling price of the product